ANALYSIS OF JUDICIAL CONSIDERATIONS IN IMPOSING PUNISHMENTS FOR NARCOTICS CRIMES (A STUDY OF DECISION NUMBER 1891/PID.SUS/2025/PN MDN) - Jeffri; Halimatul Maryani (Jurnal Ilmu Hukum dan Keadilan, 2026)
Narcotics crimes constitute an extraordinary crime that has serious impacts on security and the future of the nation’s younger generation, thereby requiring firm and just law enforcement. This research aims to analyze the application of substantive criminal law and the judicial considerations in imposing criminal sanctions on the defendant in Decision Number 1891/Pid.Sus/2025/PN Mdn, using a normative legal research method with statutory and case study approaches, supported by primary and secondary legal materials. The results of the study indicate that the application of substantive criminal law in the decision is in accordance with Law Number 35 of 2009 on Narcotics, with proof based on lawful evidence as stipulated in Article 184 of the Criminal Procedure Code (KUHAP). The judges’ considerations were carried out comprehensively by taking into account both juridical and non-juridical aspects, including the fulfillment of the elements of the offense, the role of the defendant, the type and quantity of narcotics, as well as aggravating and mitigating circumstances, so that the sentence imposed reflects the principle of proportionality and a balance between legal certainty, justice, and expediency.